PENGARUH E-WOM DAN KERAGAMAN PRODUK TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN PRODUK MAKANAN PADA PENGGUNA GOFOOD, DENGAN PRICE DISCOUNT SEBAGAI VARIABEL PEMODERASI - Komariah, Nurul Dwi; Arief, Muhammad Yahya; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2024)
This research aims to determine the significant effect of E-WoM and product diversity on purchasing intentions and purchasing decisions, as well as the significant impact of price discounts in moderating the impact of E-WoM on purchasing decisions. The data source of this research was obtained from the answers of 95 respondents. The sample determination technique used non-probability sampling, namely purposive sampling. The object of this research is Gofood users of Geprek Lek Djo and Zest Chicken. The data analysis used SmartPLS by conducting several tests namely Convergent Validity Test, Reliability Test, Classical Assumption Test, Goodness of Fit Test, Coefficient of Determination Test, Structural Equation Analysis, and Research Hypothesis Test. Test results showed that E-WoM had a positive but not significant effect on purchase intention (H1 was rejected), product diversity had a significant positive effect on purchase intention (H2 was accepted), E-WoM had a positive but not significant effect on purchase decision (H3 was rejected), product diversity had a positive but not significant effect on purchasing decisions (H4 was rejected), purchase intention had a significant positive effect on purchasing decision (H5 was accepted), price discounts had a positive but not significant effect in moderating the impact of E-WoM on purchasing decision (H6 was rejected), E-WoM had a positive but not significant effect on purchasing decision through purchase intention (H7 was rejected), product diversity had a significant effect on purchasing decision through purchase intention (H8 was accepted).